A Sensitive Colorimetric Determination of Metformin Based on Gold Nanoparticles Aggregation in Salt Solution. Issue 12 (23rd March 2022) - Liu, Wei; Li, Yongyang; Li, Lin; Shangguan, Jingfang; Liu, Yufei; Ni, Tianjun; Wang, Yaofeng; Kang, Jing
Abstract: This research attempts to explore a simple and sensitive colorimetric method to detect metformin by using synthesized gold nanoparticles (AuNPs). Spherical AuNPs were synthesized by reducing HAuCl4 with EDTA. Transmission electron microscopy (TEM) and Zeta potential were used to observe AuNPs size and solution stability before and after the addition of metformin. AuNPs became unstable and aggregated after the addition of metformin, and the absorption peak changed from 520 to 654 nm after adding metformin. NaCl concentration is an important factor in AuNPs aggregation, as low as 70 nM metformin can induce the aggregation of AuNPs under 40 mM NaCl. The linear relationship of metformin detecting was gained in the range of 150 nM∼500 nM (R 2 =0.955). The application of this method to the detection of metformin in actual samples has been verified. Therefore, AuNPs is considered to be a potential multidrug detection tool based on AuNPs surface modifiers. Abstract : AuNPs prepared by EDTA reduction showed red, and the maximum absorption wavelength was 520 nm. AuNPs with 40 mM NaCl aggregated when over 70 nM metformin was added, and the absorbance value decreased. Metformin content can be determined by changes in color and absorbance value.